HAZEL’S STRUGGLE TO GET HER SELF-ACTUALIZATION IN JOHN GREEN’S THE FAULT IN OUR STARS - Chumairoh, Putri (Balai Bahasa Jawa Timur, 2018)
This research aims to analyze John Green?s novel The Fault in Our Stars which focuses on analyzing Hazel Grace?s character and her struggle to face a stage IV cancer thyroid. The aims of this research are to describe the characteristics of Hazel Grace in The Fault in Our Stars novel and to reveal Hazel?s struggle to fulfill her needs based on Abraham Maslow?s hierarchy of need theory. The character and characterization approaches are applied as the foundation of this research. Abraham Maslow?s hierarchy of human need theory is applied as well. This theory is classified into five stages of needs which consist of physiological, safety and security, love and belongingness, self-esteem and self-actualization needs. The writer analyzed the data collected by categorizing them into five points which are included in hierarchy of needs. As a conclusion, Hazel able to fulfill her needs with her struggle as well as her self-actualization.